How can governments tax multinational enterprises more fairly? A discourse analysis. (1st October 2021) - Fernandes, Orlando; Morrell, Kevin; Heracleous, Loizos
Abstract : Extant research has identified numerous causes for multinational enterprises (MNE) tax avoidance and formulated a variety of remedial policy solutions. Yet despite being consistently decried as societally unfair, these contested practices persist. We reveal the conflicting and complementary ideologies and worldviews that reside in the background of MNE tax avoidance policy deliberations. Analysis of primary interviews with accounting and tax regulatory agencies, Members of the UK Parliament, and public hearings with MNE representatives, shows these different groups draw on four different discourses: globalism, idealism, pragmatism and shareholder interest . These exist in what we show to be a kind of precarious truce that allows these contested practices to continue in the face of robust critique. Prospects for taxing MNEs are enhanced if legislators, civil servants and regulators can draw more coherently on the discourse of idealism because this is most resistant to the logic of the market.